REGIONAL PECULIARITIES OF UNDERSTANDING PROFESSIONAL AND PERSONAL WELL-BEING BY NORTHERN TEACHERS AND ARCTIC TERRITORIES OF THE REPUBLIC OF SAKHA (YAKUTIA) - Gerasimova, Rosalia; Nikulina, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the period of socio-economic transformation of the study of regional peculiarities of understanding personal and professional wellbeing of teachers in the North and Arctic territories of the Republic of Sakha (Yakutia) are particularly pertinent given with the increase of dissatisfaction with the social and economic situation of young teachers, a reluctance to carry out their professional activities in remote territorial units of the Republic of Sakha (Yakutia). In modern conditions the welfare of an individual depends not only on the environment, material security, and mental and physical health, but also on the subjective understanding of the professional and personal welfare of teachers.Analysis of domestic and foreign scientific research allows us to note that among some of the main methodological issues of research of a phenomenon well-being is the issue of the understanding of the professional and personal well-being. However, it should be noted that the problem of psychological and pedagogical support of professional and personal well-being is complex and not well understood.Thus, the study of qualitative changes in the Outlook and attitude of teachers in the North and the Arctic gives you a holistic awareness of the impact on human reality transformation processes, and identifying qualitative changes in the personality, allowing to go deeper into issues of professional personal growth in the conditions of modernization of education, contributes effectively to determine strategic goals for professional and personal development pedagogical in terms of additional professional development.